Partisipasi Masyarakat di Kelurahan Pahandut Seberang Kota Palangka Raya dalam Pelatihan Program Green Kampung - Hamidah, Noor; Frieda; Dwi Anung Nindito; Mahdi Santoso (Fakultas Teknik Universitas Palangka Raya, 2023)
This service activity facilitates the assistance of Pahandut Seberang Village residents in realising a green village by utilising open land and yards for land media for vegetable and fruit plants. Open land and yards are used as a medium that can be planted with vegetable and fruit daily needs. The service aims to stimulate riverbank communities to utilise open land areas and yards to grow vegetables and fruit as an implementation of green villages in Pahandut Seberang Village. The Green kampung programme is planned to be located at the Daruth Tayyibah Mosque in the riverbank residential area of Pahandut Seberang Village, Pahandut District, Palangka Raya City. The method uses a qualitative method based on the process of interviewing the needs of residents, community meetings in selecting plants, planting vegetables and fruit, plant maintenance, and harvesting by the women of the Pahandut Seberang Village Recitation. The University of Palangka Raya Service Team provided assistance to the women's group in learning in the form of training from the stages of designing land, selecting plants, planting, caring for and harvesting vegetable and fruit plants. The results of this service are the implementation of green village training activities in the form of socialisation, seedling sowing, transplanting into recycled pots, and monitoring the maintenance of vegetable and fruit plants. Training activities for recitation mothers provide long-term opportunities as entrepreneurs of the riverbank community. The results of this training serve as a trigger for communities from other villages to implement the green kampung programme in the villages of Palangka Raya City.